E-Apron Movement Control (AMC) Course Module Based Web Using 4D RND Model - Auriska Wiga Pamungkas, Zalfa; Silk Moonlight, Lady; Hariyanto, Didi (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
This development research direct to determine the development process, feasibility, and responses of cadets and lecturers to electronic module-based learning media in the Apron Movement Control (AMC) course in the Air Transportation Management Diploma 3 Study Program and to produce teaching material products in the form of emodules made using the Canva Application and distributed through the LMS or Learning Management System (LMS) of the Surabaya Aviation Polytechnic. The developed learning media can be used to increase the abilities and interests of cadets in the Apron Movement Control (AMC) Course. The research and development technique used is the RnD or Research and Development method with the Four-D model. This research went through four stages of development, namely Define, Design, Development and Disseminate. The subject matter expert in this study was the Apron Movement Control (AMC) Course Lecturer, while the media expert in this study was the research advisor. In addition to being tested by media experts and material experts, the authors conducted trials through development subjects, namely Diploma 3 Air Transportation Management cadets at both Level 2 and Level 3. As an instrument for data collection in the validation of cadets and lecturers, this the study used interviews and questionnaires which would later be tested using a Likert scale. Based on the analysis of the data collected by the researcher, the validity of the material contained in the Electronic Apron Movement Control Module is 62.4%, 73.5% validity for the media and 73% for students' validity which showed that usability measurement of this E-Module “Worthy”. So that conclusion that can be drawn in this research that E-Apron Movement Control Module Based Web can be used to users.